Promoting Awareness about Psychological Consequences of Living in a Community Oppressed by the Mafia: A Group-Analytic Intervention - Giordano, Cecilia; Cannizzaro, Giusy; Tosto, Crispino; Pavia, Laura; Di Blasi, Maria (Frontiers in Psychology, 2017)
The effects of the Mafia have been extensively studied from sociological, economic, and historical points of view. However, little research has investigated the influence of the Mafia on individuals and communities in terms of its psychological and social impact. In order to contribute to the advancement of our understanding of the psychological effects of the Mafia on individuals and communities and to promote a participative process of social change, a group analytic intervention was conducted within a Community Based Participatory Research carried out in Corleone, a small Sicilian town with a historically recognized role in the evolution of the Mafia, as well as in the fight against its control. Qualitative findings from the group intervention revealed the development of an awareness process that allowed participants to become aware of their social unconscious anxieties and defenses and to recognize and manage the strong emotional impact related to the Mafia’s presence in their lives. Highlighting how psychological processes can have negative impacts on individual and collective capacity to pursuit transformation and resilience, this article provides important insight on how clinical psychology may operate in socio-cultural contexts to promote the reconstruction of the traumatic social dimensions in the community.